Pengembangan SSP HOTS untuk meningkatkan Karakter dan hasil belajar peserta didik Kelas V SD - Masnur Masnur; Nadar Nadar (Edumaspul: Jurnal Pendidikan, 2020)
This research aims to produce learning devices in the form of Subject Specifik Pedagogy (SSP) based on Higher Order Thinking Skills (HOTS) to improve the character and learning outcomes of students in Grade V Elementary School. This research is research and development, consisting of nine stages, namely: (1) research and data collection, (2) planning, (3) product draft development, (4) initial field trials, (5) revising field trial results, (6) field trials, (7) improvement of field trial products, (8) field execution trials and (9) final product enhancements. The test subjects were grade V students of SDN 8 Pinrang. One-on-one trial subjects consisted of 3 learners. Small group trial subjects consisted of 10 students who had not been involved in one-on-one trials, and field trial subjects consisted of 30 V.B. Class students. This research is expected to contribute to academics in improving the character and learning outcomes of students